Simulation and Implementation of Robot Obstacle Avoidance Algorithm on ROS - Zhang, Jiaonan; Zhang, Tengyu; Niu, Yi; Guo, Yuxuan; Xia, Jiahao; Qiu, Yang; Yuan, Zhengyi; Yang, Yingze (Journal of physics. Conference series, 2022)
Robots often collide in the process of simulation soccer match. The collision will block the robot’s own motion trajectory, which is not conducive to the robot’s ball grasping and defense. Considering that the obstacles have the characteristics of dynamics, antagonism and uncertainty, the robot’s motion trajectory, path selection and obstacle avoidance are very important. Taking ROS as the research platform, the study focuses on the path planning of simulated soccer robot. Meanwhile, we have applied some obstacle avoidance algorithms to the Middle Size Simulation League of soccer.